Patient Safety and Care After Outpatient Endoscopic Retrograde Cholangiopancreatography (ERCP): A Single-Center Experience in Germany - Vu Trung, Kien; Feisthammel, Juergen; Hoffmeister, Albrecht; Karlas, Thomas (Zeitschrift für Gastroenterologie, 2025)
The current goal of adapting care structures in the German healthcare system is to increase the provision of interventional treatments in outpatient settings. Endoscopic Retrograde Cholangiopancreatography (ERCP) procedures were traditionally performed in an inpatient setting until 2022. However, with the introduction of a new Ambulatory Surgery Contract (according to Section 115b, Paragraph 1 of the Social Code, Book V) on January 1, 2023, these procedures are now intended to be carried out more strictly on an outpatient basis, meaning that hospitalization will no longer be reimbursed in most cases.Between June 1, 2023, and December 31, 2023 all ERCP procedures performed in an outpatient setting were included in this study. This cohort had standard ERCP indications and a low comorbidity burden according to the §115b specifications. Using propensity score matching (nearest-neighbor), these cases were matched with patients who underwent ERCP procedures in an inpatient setting between June 1, 2022, and December 31, 2022.Propensity-score matching identified a cohort of 166 patients (83 outpatients and 83 inpatients) with similar baseline characteristics. The most common indications for ERCP were choledocholithiasis and biliary strictures. Reported complications comprised pancreatitis, bleeding and cholangitis and were rare in both groups, occurring in 7% of inpatient procedures and in 6% of outpatient procedures. The latter cases required inpatient admission after self-presenting to the emergency department. No serious adverse events were reported.Outpatient ERCP is a safe procedure for selected patients with a low risk profile. Complications occurred rarely and could be adequately managed.
Keywords: ERCP; Endoscopy; bile duct